Estudo e desenvolvimento do índice potencial de impacto de descargas atmosféricas em linhas de transmissão - Borges, Fábio Célio Carneiro da Silva [UNESP] (2014)
The forecast of atmospheric electrical discharges is a challenge in Physics and related Sciences. It is known that field campaigns and installation of the sensor network have shown great precision degree by the historical of the observation. Despite having large amount of data, we have had many scientific papers on modeling of lightning towers in electric transmission lines. This work aims to do a study for obtaining a Potential Index of Impacts Lightning in Electric Transmission Lines. In order to get this Index, an accurate factorial experiment was combined with regional forecast models output. As a result, although the discovery can be used for diagnosis and tornadoes forecasting, its has not been concluded by this work target yet. Having shown the technique can help the modeling research, an expansion of sample as well as new experiment and news research can contribute more for Index improvement